Los estereotipos del hombre y la mujer en una novela publicada en 1622: "El andrógino", de Francisco de Lugo y Dávila - Copello, Fernando (El Colegio de México, 2008)
This article examines the representation of sexual identity in a 17th century Spanish novel by Francisco de Lugo y Dávila. The writer follows several cultural stereotypes so as to build a very atractive story for this audience. But the story is quite mysterious too. El andrógino is based on two fictions by Cervantes and Firenzuola.